Activities Undertaken at the Central Department of Geography: 2008-2010 - Pradhan, Pushkar K (Geographical Journal of Nepal, 2009)
Introduction: The Central Department of Geography (CDG) at Kirtipur is one of the leading Departments of the Faculty of Humanities and Social Sciences, Tribhuvan University. The Department was established in 1958. Since then, it has been actively serving the country in higher education and research. CDG runs regular Master’s and PhD programmes in Geography. It is a pioneer Department in running courses - Geographic Information System (GIS) and Remote Sensing (RS) in the country. Being a central department, it has to look after the academic programmes and activities of 22 Departments of Geography under the Tribhuvan University’s constituent campuses spreading across different parts of the country, where there are proficiency certificate and bachelor level studies. Of these, the Department of Geography at Prithvi Narayan Campus, Pokhara also runs regular Master’s degree, in addition to proficiency certificate and bachelor levels. This paper portrays the academic activities concerning with strengthening of geography subject being held at CDG from October 2008 onward. The Geographical Journal of Nepal, Vol. 7, 2009: 61-66